Folk Ballad beyond the Genre Definition - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2022)
The ballad has long existed in the periphery of the Lithuanian folkloristics. In this article, the folk ballad’s role and place in the Lithuanian folksong tradition is explored discussing two classical works of the Lithuanian folklore research characterized by their rather diverse theoretical assumptions. Both works were published in the end of the 1960s. The first one is the study on the Lithuanian folk ballads by Pranė Jokimaitienė (1968), and the second one is the monograph by Donatas Sauka discussing the uniqueness and value of folklore (1970). The author of the article suggests examining the folk ballad not only in terms of the genre, but also from the broader interdisciplinary perspective, thus combining both above-mentioned points of view by Jokimaitienė and Sauka. Such approach is strengthened by the research history of the ballad – a very complex and complicated phenomenon.Limiting the ballad analysis exclusively by the Lithuanian material on the one hand, and by the pure folklore on the other, hinders us from adequately placing the ballad in the Lithuanian folklore system. Therefore, the author suggests renouncing the narrow concept of the ballad as a text, at the same time regarding it beyond the definition of the genre and taking into account its social, cultural, historical and anthropological contexts. The article aims at discussing the peculiarities of the ballads’ existence in the Lithuanian environment in terms of development of the Lithuanian folkloristics. Notably, ballads have always found themselves at the outskirts of the idealizing template of the research in Lithuanian folksong.Various nations have seen very diverse adaptations of the ballad plots, and this international diversity of folk ballads along with their dissemination across other genres opposes making clear decisions regarding their identity, even when the general definition is applied. Giving in to the temptation of submitting the generic definition, the folklorist adopts the views of a literary scholar: the definition might look essentially correct (the ballad is “a lyric-epic composition characterized by dramatic features” or “a narrative folksong with lyrical and dramatic character”, etc.), but will hardly be of use. Compositions with similar plots might be attributed to different genres in various national folklores, which works according to their own folklore systems. Besides, even variants of the same type might embrace a rather broad scope: from the stylistically pure ballads to the lyric transformations with ballad motives. This complicates the wish to combine all compositions and types into a single generic group. Here, one must bear in mind the already established tradition of folklore research. In Lithuania, development of folkloristics has shaped a general image of the folklore universe, which has in turn dictated how the whole folksong corpus is ordered and systematized.Finally, the author draws the readers’ attention to the fact that ballads – the folksong layer of foreign origins and abounding in signs of “otherness” – have become unique compositions in Lithuania, not similar either to European samples nor to the authentic canonic Lithuanian folksongs. Having appropriated a topic or some wandering story line, Lithuanians frequently do their own transformations in terms of content and form. It is concluded that the Lithuanian ballads have sprung from interactions between the local folksong tradition and the balladic expression, thus acquiring an additional meaning and value.
Keywords: folk ballads; Lithuanian folksong tradition; balladic expression; folksong research; genre